Future preferences and prospection of future of outcomes: Independent yet specific associations with attention‐deficit/hyperactivity disorder. (18th July 2020) - Kostyrka‐Allchorne, Katarzyna; Cooper, Nicholas R.; Wass, Sam V.; Fenner, Benjamin; Gooding, Peter; Hussain, Sahir; Rao, Vidya; Sonuga‐Barke, Edmund J.S.
ABSTRACT: Introduction: Symptoms of attention‐deficit hyperactivity disorder (ADHD) and conduct problems have been associated with heightened temporal discounting of reward value resulting in a preference for immediate over delayed outcomes. We examined the cross‐sectional relationship between future preference (including intertemporal choice) and prospection (the ability to bring to mind and imagine the experience of future personally‐relevant events and outcomes) in adolescents with a range of ADHD symptoms and aggressive behaviour. Methods: A combination of behavioural tasks and self‐reports measured intertemporal decision making, individual differences in preference for future outcomes and experience of prospection in a convenience sample of English adolescents aged 11–17 (n = 64, 43.8% males). Parents rated symptoms of ADHD and aggression. Results: & Conclusions : Factor analysis identified two factors: "Future Preference" and "Prospection". Significant negative bivariate correlations were found between ADHD and the scores of both factors and between aggression and Future Preference. A path model confirmed the independent significant association of ADHD with both factors but not with aggression. There was no evidence that Prospection was associated with Future Preference or that it reduced the associations between ADHD symptoms and Future Preference. These results provide further evidence that ADHD is associated with a tendency to prefer immediate over future outcomes. The same association with aggression seemed to be driven by the overlap with ADHD symptoms. We provide some of the first evidence that individuals with high ADHD symptoms have difficulty in prospecting about future episodes. However, this is unrelated to their preference for future outcomes.